Canopy for the Tram and Bus Stop "Krefeld Ostwall" - M. Kramer (Challenging Glass Conference, 2016)
The „Ostwall“, one of Krefeld‘s most important public traffic intersections, is getting modernized completely for the moment. The highlight of the project is the new canopy for the tram and bus stop. It was decided to realize a steel-glass structure, to get most possible transparency. The structure has a length of 125m and a width of 12m. The main structure has 9 column brackets, that are bearing a space truss. These elements are made of steel. For the roofing, partially curved glass elements are used, that are bonded to a stainless steel frame by structural silicone. The slope of the roofing reaches to the gutter in the middle axis of the building. For each side, only one glass element is used, to guarantee a good flow of rain water. The glass elements have a developed length of 5.2m and a width of 2.2m. At the front ends of the structure, spherically curved glass elements are used. The glass roof is accessible for cleaning and inspection work. To get a smooth view of the bottom surface, the glass is bonded under the steel frame, so the silicone bonding is used to bear the self-weight of the glass elements. The pre-fabricated elements are fixed to the main structure at the bottom girder of the framework directly, and at the top girder by a suspension bar. To get a minimized cross section of the stainless steel bars, they are stabilized by the glass elements to prevent them from torsional-flexural buckling.